Demystifying the Human Trafficking from the Human Rights Perspectives: A Comprehensive Review - Barako, Basha Bekele (International Journal of Law and Public Policy (IJLAPP), 2023)
Human trafficking is presently catching the attention of most governments and international organizations owing to its severe health consequences and issuant social crisis. It is thus resulting in severe impacts on the lives of trafficked people who are susceptibly in a condition beyond their control. More desperately, the problem is worsened because most governments and institutions haven’t taken the problem from the human rights perspectives. This particular particle makes a comprehensive review on the human trafficking from the human rights perspectives. After reviewing different literatures it was found that the human right violation on the trafficked person is committed in different stages of the process either by the government and traffickers themselves. Therefore, the responses against the human trafficking should make the human rights at the center.